Terahertz photoconductive atomic force microscopy of few-layer graphene flakes - Fragomeni, Erica; Berkmann, Fritz; Temperini, Maria Eleonora; Baldassarre, Leonetta; Ortolani, Michele; Giliberti, Valeria; Venanzi, Tommaso (Frontiers in Photonics, 2025)
Reaching nanometric spatial resolution in terahertz (THz) nanoimaging provides a powerful tool for the characterization of photonic devices. Here, we couple a THz source to a conductive atomic force microscope to measure the THz photo-induced current with nanometric spatial resolution. We aim at measuring the THz photo-induced current of few-layer graphene flakes with a platinum nanometric probe that acts both as THz field-enhancement antenna and as metal counter-electrode that forms a nanojunction. The THz beam is generated at 0.61 THz by an amplifier-multiplier chain. THz photo-induced current signals are detected and compared with the current-voltage characteristics. With this method, we map nanometric charge puddles in few-layer graphene flakes, and observe evidence of THz rectification at the platinum-graphene nanojunction. The local junction characteristic can be used to assess the surface quality of 2D-material flakes.